Electrochemical impedance spectroscopy as a micropropagation monitoring tool for plants: A case study of tamarillo Solanum betaceum callus - André Caeiro; Jorge Canhoto; Paulo R.F. Rocha (iScience)
Summary: Tamarillo is an economically important species that has been extensively studied in terms of in vitro morphogenesis and micropropagation techniques, including somatic embryogenesis. Callus cultures are used to characterize plant growth and differentiation as well as the production of secondary metabolites. In all cases, real-time screening methods to characterize cellular growth remain poorly explored. Here, we show that electrochemical impedance spectroscopy (EIS) enables non-invasive and real-time monitoring of callus growth and cytological changes. A non-embryogenic callus line derived from leaf explants of tamarillo was used. The callus was tested in both standard culture medium containing the auxin picloram and in auxin-free medium. The low frequency impedance modulus and the equivalent circuit charge transfer resistance are found to effectively translate real-time cellular growth and microstructural deformations which have been benchmarked with light and scanning electron microscopy and mass measurements. EIS therefore emerges as a micropropagation monitoring technique in plant biotechnology.